Topographic Characteristics of Ramganga River Basin : Digital Elevation Model and GIS Based Study - Mukherjee, Rameswar; Bilas, Ram (National Geographical Journal of India, 2022)
Surface topography of any drainage basin plays an important role in the development of drainage networks and its evolution. Basin hydrology is also controlled by topographic attributes as the overland flow, through flow and stream flow are largely determined by relief and slope. Topography largely affects the evolution of landforms and slope, vegetation growth, and soil development. So it is necessary to quantify the various parameters of topography in order to get the economic design for river utilization and control, as well as watershed development and planning. In the present study an attempt has been made to evaluate existing topographic condition of the Ramganga River Basin by using ASTER GDEM data. Geographic Information System (GIS) was used for calculating and mapping. The study reveals that the nature and variations of surface and relief parameters are largely affected by the topographic variability.